REAL-TIME MOTION IMAGE POSE DECOMPOSITION, CLASSIFICATION AND ANALYSIS - Huang, Chien-Hsing (International Journal of Engineering Technologies and Management Research, 2024)
Exercise can boost metabolism and make the body healthier. It also increases metabolic rate, helping to consume more calories and burn fat. Regular exercise can stimulate the brain to secrete endorphins, making people feel relaxed and happy, and improves self-confidence, and has been shown to reduce symptoms in people with depression and anxiety. However, incorrect exercise posture may cause harm to the body, such as torn ligaments or muscle strains, so good exercise posture is needed to improve sports performance. This article proposes to use artificial intelligence image analysis method to decompose fitness exercise posture images and establish exercise posture cycle samples to assist in completing fitness exercises.